How long are The Survival Time in the Industrial Sector of Indonesian Companies? - Titik Kristanti, Farida; Isynuwardhana, Deannes (International Journal of Engineering and Technology, 2018)
Cox Hazard model with time independent covariates is used to view the functions of survival and hazard for each group of industrial sector of companies listed on the Indonesia Stock Exchange. The hazard explains whether events of financial distress will occur in companies that have survived for a certain period. The survival function shows the relationship between probabilities to survive and time, in which time indicates the duration of an event (financial distress). The results of statistical analysis show that the survival time for each industrial group varies from 10.5 to 12.5 years. The results can be used as a basic idea for companies to determine when the preventive actions should be conducted so that companies will sustain their business. Â Â